Association of symptomatic upper respiratory tract infections with the alteration of the oropharyngeal microbiome in a cohort of school children in Côte d’Ivoire - Missa, Kouassi Firmin; Diallo, Kanny; Bla, Kouakou Brice; Tuo, Kolotioloman Jérémie; Gboko, Kossia Debia Thérèse; Tiémélé, Laurent-Simon; Ouattara, Allassane Foungoye; Gragnon, Biego Guillaume; Ngoi, Joyce Mwongeli; Wilkinson, Robert J.; Awandare, Gordon A.; Bonfoh, Bassirou (Frontiers in Microbiology, 2024)
The oropharyngeal microbiome plays an important role in protection against infectious agents when in balance. Despite use of vaccines and antibiotic therapy to prevent respiratory tract infections, they remain one of the major causes of mortality and morbidity in Low- and middle-income countries. Hence the need to explore other approaches to prevention by identifying microbial biomarkers that could be leveraged to modify the microbiota in order to enhance protection against pathogenic bacteria. The aim of this study was to analyse the oropharyngeal microbiome (OPM) of schoolchildren in Côte d'Ivoire presenting symptoms of upper respiratory tract infections (URTI) for better prevention strategy. Primary schools’ children in Korhogo (n=37) and Abidjan (n=39) were followed for six months with monthly oropharyngeal sampling. Clinical diagnostic of URT infection was performed and nucleic acid extracted from oropharyngeal swabs were used for 16S rRNA metagenomic analysis and RT-PCR. The clinical examination of children’s throat in Abidjan and Korhogo identified respectively 17 (43.59%) and 15 (40.54%) participants with visible symptoms of URTIs, with 26 episodes of infection in Abidjan and 24 in Korhogo. Carriage of Haemophilus influenzae (12%), Streptococcus pneumoniae (6%) and SARS-CoV-2 (6%) was confirmed by PCR. A significant difference in alpha diversity was found between children colonised by S. pneumoniae and those that were not (p=0.022). There was also a significant difference in alpha diversity between children colonised with H. influenzae and those who were not (p=0.017). No significant difference was found for SARS-CoV-2. Sphingomonas, Ralstonia and Rothia were significantly enriched in non-carriers of S. pneumoniae; Actinobacillus was significantly enriched in non-carriers of H. influenzae; Actinobacillus and Porphyromonas were significantly enriched in non-carriers of SARS-CoV-2 (p<0.001). Nearly 40% of children showed clinical symptoms of infection not related to geographical location. The OPM showed an imbalance during H. influenzae and S. pneumoniae carriage. This study provides a baseline understanding of microbiome markers in URTIs in children for future research, to develop targeted interventions aimed at restoring the microbial balance and reducing the symptoms associated with RTIs.